Investigating the Use of WhatsAuto for Students' Consultation on Writing Narrative Project at X Grade SMK Muhammadiyah Tepus 2023 - Subangun, Rohmat; Susanti, Ani; Oktavianti, Ikmi Nur (Journal Corner of Education, Linguistics, and Literature, 2025)
The study aimed to investigate the implementation process, benefits, and obstacles of using WhatsApp Automatic Reply (WhatsAuto) for students' consultation on writing narrative projects at X Grade SMK Muhammadiyah Tepus 2023. This descriptive qualitative research involved an English teacher and students from the X Grade as participants. Data collection methods included interviews, classroom observations, and documentation. The findings reveal that using WhatsAuto was conducted through structured activities divided into three stages: classroom activity, crosscheck, and submission. These stages allowed continuous interaction between students and teachers, supporting online and offline learning environments. The use of WhatsAuto provided several benefits, such as instant accessibility, flexibility, efficient communication, personalized learning experiences, and the promotion of digital literacy. However, some obstacles were identified, including varied levels of student understanding, low motivation, and technical issues such as poor network connectivity.